THE EFFECT OF STORYTELLING TECHNIQUE ON THE SPEAKING ABILITY OF THE THIRD YEAR STUDENTS OF SMP N 1 BENAI - Polia, Anona; Eliwarti, Eliwarti; Mahdum, Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know the effect of storytelling technique on student’s speaking ability of the third year students of SMP N 1 Benai. This research was pre-experimental design involving 22 students as a sample chosen through cluster random sampling. The data were gained before and after the treatment implementing storytelling technique. The students were given pre-test and post-test. The average score for pre-test was 46.54 and the average score for post-test was 63.21. The data shows that there are an increass from the pre-test and the post-test. The data analysis shows that the t-test is higher than t-table (7.517> 2.08).The result of this research shows that storytelling technique had an effect on students’ speaking ability because there was a significant difference between the post-test and pre-test. It shows that the storytelling technique could help the students to improve their speaking ability. Related to this research the aspect of fluency has the highest different score then, grammar and pronunciation has the lowest score. Thus, the learning process need to focus on that aspects.